PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN KSP SURYA MANDIRI DI DESA BATUAN KALER KECAMATAN SUKAWATI - I Made Ranji Ari Rahmadi; Pande Ketut Ribek; Tiksnayana Vipraprastha (VALUES, 2024)
Human resources are really needed by companies as system managers and subjects of implementing company policies and operational activities to achieve predetermined goals. If human resources are managed well, they can support the business success of a company or cooperative. In a company, human resources are very necessary to act as drivers for the various kinds of work that will be carried out by employees. The factors that influence performance consist of work motivation, work discipline and work environment on employee performance. This research aims to test and analyze the influence of work motivation, work discipline and work environment on employee performance. This research was conducted at the Surya Mandiri J1 Savings and Loans Cooperative. Raya Sakah. Batuan Kaler, Sukawati, Gianyar, Bali 80582. The object of this research study is the object of study which is the focus of attention of a research study. The object of this research study is the influence of work motivation, work discipline and work environment on employee performance. The population in this study included 45 employees and female employees who worked at KSP. Surya Mandiri. The sampling method used in this research is saturated sampling or census, that is, the entire population is sampled. The types of data used in this research are quantitative data and qualitative data. The data sources used in this research can be classified into two, namely primary data and secondary data. All data obtained from the questionnaire distribution is suitable for use, then analyzed using multiple linear regression, hypothesis testing (t test and f test). The research results show that (1) Work motivation has a positive and significant effect on employee performance at KSP Surya Mandiri Sukawati, so that the more work motivation increases, the more employee performance at KSP Surya Mandiri Sukawati increases. (2) Work discipline has a positive and significant effect on employee performance at KSP Surya Mandiri Sukawati so that the better the work discipline, the more employee performance at KSP Surya Mandiri Sukawati will increase. (3) The work environment has a positive and significant effect on employee performance at KSP Surya Mandiri Sukawati, so that the more the work environment improves, the more employee performance at KSP Surya Mandiri Sukawati will increase.